Monitoring the endemic ornamental fish Pterapogon kauderni in Bokan Kepulauan, Banggai marine protected area, Indonesia - Samliok Ndobe; Kris Handoko; Deddy Wahyudi; Moh. Yasir; Yulina Irawati; Wendy Alexander Tanod; Abigail Mary Moore (Depik, 2020)
Abstract. The Banggai cardinalfish Pterapogon kauderni is a species of national and international conservation concern. Established in November 2019, the Banggai marine protected area (MPA) in Central Sulawesi, Indonesia covers most of the endemic range of this ornamental fish. The third repeat survey (T2 monitoring) under the National Action Plan for Banggai Cardinalfish Conservation (NAP-BCFC) was carried out in October 2019 at eight sites in the Bokan Kepulauan region within the MPA. The T2 monitoring used the standard NAP-BCFC belt transect method. Data were collected on P. kauderni abundance (by size class: recruits, juveniles, adults) and microhabitat (sea urchins, sea anemones, hard corals, and others). Data were evaluated with respect to the T0 (2017) survey and T1 (2018) monitoring at the same sites, as well as previous surveys in 2004 (2 sites) and 2012 (4 sites). The data show wide between-site variation in P. kauderni and microhabitat parameters, with one subpopulation at very high risk of extirpation. Trends included declines over time in P. kauderni, sea urchin and sea anemone abundance, with an increase since 2017 in hard coral microhabitat use by adult P. kauderni. We recommend evaluation of other P. kauderni populations in Bokan Kepulauan and specific site or zone-based actions. However, we conclude that the most urgent priority for P. kauderni conservation in Bokan Kepulauan is protection of key microhabitat through a moratorium on sea urchin and sea anemone collection in P. kauderni habitat.  Keywords: Banggai cardinalfish, endangered species, marine conservation, microhabitat, monitoring, ornamental fishery, CITES